Mechanisms and Clinical Research Progress of Rituximab in the Treatment of Adult Minimal Change Disease - Zheng, Yin; Haofei, Hu; Qijun, Wan (Journal of Clinical Nephrology, 2023)
Introduction: Minimal change disease (MCD) is a common subtype of primary nephrotic syndrome in adults. The pathogenesis of MCD is still not well understood, but some studies suggest that MCD is a T cell-mediated disease related to podocyte dysfunction. Previous research has also indicated the crucial role of B cells in the pathogenesis of MCD. Rituximab (RTX) is a recombinant chimeric mouse/human antibody targeting CD20 antigen. In recent years, RTX has been increasingly used in adult MCD patients. Methodology: We searched the PubMed database using the keywords “Minimal change disease”, “Nephrotic syndrome”, and “Rituximab” and obtained a total of 140 articles. We will now provide a literature review based on these 140 articles, according to our research topic. Discussion: This article provides an overview of the mechanisms and clinical research progress of RTX in the treatment of adult MCD. We have also discussed the current treatment methods for MCD, exploring the potential of using RTX as a first-line therapy for refractory adult MCD. Conclusion: MCD is a common pathological type of nephrotic syndrome, and the exact mechanisms are still not fully understood. Although RTX as a treatment of adult MCD has shown promising clinical results in patients with refractory adult MCD, the safety and efficacy of RTX still lack high-quality clinical evidence. Further research is needed to explore the pathogenesis of MCD and the RTX treatment for MCD.